2018
DOI: 10.1055/s-0038-1676303
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Cytochrome P450 2D6 (CYP2D6) Genetic Polymorphism in Tamoxifen Therapy for Breast Cancer

Abstract: Tamoxifen (TMX) is the main drug used both in pre and postmenopausal women as adjuvant treatment for hormone receptor-positive breast cancer. An important barrier to the use of TMX is the development of drug resistance caused by molecular processes related to genetic and epigenetic mechanisms, such as the actions of cytochrome P450 2D6 (CYP2D6) polymorphisms and of its metabolites. The present study aimed to review recent findings related to the impact of CYP2D6 polymorphisms and how they can affect the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
(129 reference statements)
0
7
0
1
Order By: Relevance
“…Genetic variants of CYP2D6 can be classified based on the activity of the enzyme as extensive, intermediate and poor metabolisers and these genotypes have a gene-dose effect on the endoxifen concentrations in patients treated with tamoxifen [72]. In a study conducted by Blancas et al in 2018, a significantly lower disease-free survival was observed in a set of 87 patients taking adjuvant tamoxifen treatment with slow metabolisers compared to the rapid counterparts [73]; we refer the reader to in-depth reviews [74,75] of how the variant alleles of CYP2D6 can be used to predict the outcome in tamoxifen-treated breast cancer patients. A recent study conducted with data from Swedish breast cancer cohorts demonstrated a worse prognosis for both rapid and slow metabolisers (compared to normal), which could be due to the occurrence of adverse effects of the treatment [76].…”
Section: Cyp2d6mentioning
confidence: 99%
“…Genetic variants of CYP2D6 can be classified based on the activity of the enzyme as extensive, intermediate and poor metabolisers and these genotypes have a gene-dose effect on the endoxifen concentrations in patients treated with tamoxifen [72]. In a study conducted by Blancas et al in 2018, a significantly lower disease-free survival was observed in a set of 87 patients taking adjuvant tamoxifen treatment with slow metabolisers compared to the rapid counterparts [73]; we refer the reader to in-depth reviews [74,75] of how the variant alleles of CYP2D6 can be used to predict the outcome in tamoxifen-treated breast cancer patients. A recent study conducted with data from Swedish breast cancer cohorts demonstrated a worse prognosis for both rapid and slow metabolisers (compared to normal), which could be due to the occurrence of adverse effects of the treatment [76].…”
Section: Cyp2d6mentioning
confidence: 99%
“…Moreover, drug effects can be different among people and depending upon several genetic factors. Alterations in tamoxifen metabolism have been studied as possible causes of different responses to this therapy [32]. Another important role in triggering resistance to endocrine therapies in BC has been played by growth factors and their receptor signaling pathways, being able to activate ERα in absence of ligand [33].…”
Section: Mechanisms Of Endocrine Resistance In Breast Cancermentioning
confidence: 99%
“…For some alleles, similar frequencies have been determined among African Americans, East Asians, and Europeans [20,21,22]. Genetic variations on CYP2D6 are associated with reduced concentration of endoxifen [1] due to reduced CYP2D6 enzyme activity [23]. Since endoxifen have about 100-fold more affinity for estrogen receptor than tamoxifen, the effectiveness of tamoxifen is affected by the decrease in the concentration of endoxifen.…”
Section: Introductionmentioning
confidence: 96%
“…Individual genetic characteristics are known to influence drug response. The reasons may vary and include different adsorption capacities, absence of specific drug metabolic enzymes, or even polymorphisms regarding drug metabolism [1,2]. Additionally, therapeutic doses concentration in the blood are influenced by genetic matrix, causing extremely high or extremely low scenarios, and thus leading to serious side effects, including death [3].…”
Section: Introductionmentioning
confidence: 99%